Non-native barnacle accelerates the recovery from disturbance of intertidal mussel beds - Soria, Sabrina Andrea (2024)
The barnacle Balanus glandula is a non-native species inhabiting Argentinian rocky shores. The native mussel Brachidontes rodriguezii forms extensive beds in the mid-intertidal zone of these shores, generating a physical structure that determines the diversity of the assemblage. Yet, this native foundation species is prone to mortality due to disturbances associated with extreme climatic events. The aim of this study was to experimentally investigate the role of early-colonizing, non-native B. glandula in the succession process and the recovery of mussel beds following disturbance. Experimental plots were demarcated in the mussel bed and initially cleared of mussels, to produce exposed rock surfaces similar to those that form after a disturbance event. Half of these plots were kept barnacle-free throughout the experiment by removing all recruiting B. glandula, whereas all recruits were allowed to develop in the remaining plots. Our results showed that mussel cover at the end of the experiment was higher in the plots with barnacles. The plots with and without barnacles followed different successional trajectories, with increasing limpet densities and reduced cover of crustose algae in the presence of barnacles during early successional stages. The results indicate that the presence of B. glandula at the early stages of succession can alter successional dynamics and facilitate the recovery of mussel bed cover after disturbance events. More broadly, this study also shows that non-native species, although frequently considered a ‘nuisance’, can accelerate the recovery of foundation species that characterize entire communities and sustain the greatest share of their diversity.